Superparamagnetic nanocomposite of magnetite and activated carbon for removal of dyes from waste water - Thakuria, Pankaj; Joy, Pattayil Alias (Nanoscience and Nanotechnology Letters, 2009)
Nanocomposite of superparamagnetic Fe(3)O(4) and activated carbon (AC) is synthesized at room temperature and characterized by various techniques. Magnetic measurements indicated that the Fe(3)O(4) nanoparticles are isolated by the AC particles. The magnetic fluid obtained by dispersion of the nanocomposite in water is found to be relatively stable. The dispersion is found to be very efficient for the removal of methylene blue dye from water. Thus, the nanocomposite is highly suitable for removing dissolved dyes and other contaminants from waste water by a simple magnetic separation process after adsorption on AC.
Keywords: Magnetic Separation; Nanocomposite; Superparamagnetism; Water Purification

High room temperature ferromagnetic moment of Ho substituted nanocrystalline BiFeO3 - Thakuria, Pankaj; Joy, Pattayil Alias (Applied Physics Letters, 2010)
Magnetic properties of trivalent rare-earth ion substituted nanocrystalline BiFeO3 have been studied for the compositions Bi0.875R0.125FeO3 (R=La, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, and Yb). All compositions show ferromagnetic characteristics at room temperature, with enhanced magnetization after substitution. Very high magnetization (at 6 T), almost three times that of the unsubstituted composition, is observed for R=Ho, and highest remnant magnetization is obtained for R=Nd and Sm. The magnetic transition temperature is increased by similar to 20 K for R=La. The results show that it is possible to tune the magnetic characteristics of the nanocrystalline multiferroic BiFeO3 by the choice of the rare-earth ion. (C) 2010 American Institute of Physics. [doi: 10.1063/1.3502481]